A testing platform for subsea power cable deployment. (February 2019) - Reda, Ahmed; Abu-Siada, Ahmed; Howard, Ian M.; McKee, Kristoffer K.
Abstract: The failure of subsea cables has been predominantly attributed to third party activities and cable field joints. Field joints may be unavoidable due to joining of insufficient factory-made cable lengths, cable repair, or when the cable installation process has to be abandoned due to rough weather or other unplanned events. Failures within the jointing location reveal that current quality testing of these joints may be inadequate. The failure mode in these joints is mainly a result of seawater ingress at the field joint. Current design practices for subsea cable field joints recommend offshore simulations/trials to demonstrate the long term performance of the joint under the expected mechanical loads during cable installation to demonstrate whether the planned field joining practice is satisfactory. Nevertheless, offshore simulations are costly, and therefore a set of standardized onshore testing schemes would be advantageous alternative. This paper presents an onshore testing scheme for subsea power cable deployment. The proposed testing arrangement can be employed to verify the design of the offshore field joint and to prove the functionality of the field joint under the installation loads.